Pre- and Post-COVID-19: The impact of US, UK, and European stock markets on ASEAN-5 stock markets - Izaan Jamil; Mori Kogid; Lim, Thien Sang; Jaratin Lily (MDPI, 2023)
This study investigates the relationship between closing–opening prices of stocks in the US, UK, and European markets and the prices of stocks in the five Association of Southeast Asian Nations (ASEAN-5) markets, a group consisting of five founding members, namely, Indonesia, Malaysia, the Philippines, Singapore, and Thailand. In particular, this study examines the impact of US, UK, and European stock market movements on ASEAN-5 stock markets before and during the COVID-19 pandemic. An autoregressive distributed lag (ARDL) bounds testing approach was employed on two independent data sets, representing prices of stocks before and during the COVID-19 pandemic. The results reveal that among the ASEAN-5 markets, only the Philippines had a cointegration relationship with the US, UK, and European markets before the crisis. However, almost all ASEAN-5 markets moved in tandem with the US, UK, and European markets during COVID-19, except for Thailand. These empirical findings also indicate that the stock markets in the two regions tended to co-move during the COVID-19 pandemic, implying a contagion effect. Further, the causality results also provide substantial evidence of contagion between markets during the pandemic. These results imply that the stock markets in ASEAN 5 are susceptible at the opening bell to the behaviour of US, UK, and European stocks. Therefore, investors or traders in ASEAN-5 should participate in foreign markets (other than the US, UK, and Europe) that do not exhibit cointegration relationships to better mitigate and manage risk at the opening bell, especially during a global crisis.